Increasing character strength knowledge, interest, and skill: preliminary evidence for a collaborative and multimethod assessment procedure - Klibert, Jeffrey; Simpson, Michaela; Weiss, Brandon; Yancey, C. Thresa; Pritulsky, Calla; Luna, Amy; Houseman, Hayley; Samawi, Hani (Frontiers in Psychology, 2023)
The objective of this study was to evaluate whether a qualitative, collaborative, and multimethod assessment protocol increased reports of character strength interest, knowledge, and perceived skills. Thirty-two participants completed three phases of data collection. Participants were first screened for well-being, which was used as an auxiliary covariate to order participants into experimental conditions. Selected participants were randomly assigned to a control or collaborative and multimethod assessment (card sort x qualitative interview) condition. Participants completed pre- and post-measures of strength interest, knowledge, and perceived skill. In the final phase, participants who completed the second phase were invited to report on strength-related outcomes 24 hours post-administration using an online survey. A series of 2 (Assessment Condition) x 3 (Time) mixed ANOVAs were analyzed. Results revealed a significant assessment condition by time interaction for strength knowledge and perceived skill. Participants in the collaborative and multimethod assessment condition reported higher strength knowledge and perceived skills compared to control participants. These effects were maintained for 24 hours. The findings offer preliminary yet sizable support for use of collaborative and multimethod assessment procedures to increase strength knowledge and perceived skill. Because of the qualitative, collaborative, and individualized nature of our assessment protocol, the findings offer a low-cost and contextually bound pathway to increase strength-based outcomes.